IMPLEMENTATION OF GREEN ARCHITECTURE CONCEPT IN MOSQUE DESIGN : A FACE AND ISLAMIC DA’WAH - Try Ramadhan; Heru Wibowo; Rahy R. Soekardi; Dianna Astrid Hertoety (Indonesian Journal of Built Environmental and Sustainability, 2019)
ABSTRACT : Mosque as a means of worship is very important for Indonesian people who are Muslim majority. Mosques in Indonesia have been numerous and will continue to grow. Environmental issues due to the many building developments have become a global concern today, from the limited natural resources, global warming, climate change, Urban Heat Island (UHI) to its impact on the comfort and health of people. The concept of green architecture has been used to minimize environmental damage from buildings. This design-based research will implement green architecture approach in the mosque design in the context of a particular location to identify problems, possible applications and potential development. The designated location is in the eastern area of Bandung, city gates that has fairly dense place of settlement and transportation.The results showed that green architecture approach with neighborhood perspective criteria can be applied, especially with large scale mosque such as the case. The approach is more holistic and relates to the type of communal building. Criterias such as (1)land ecological enchancement; (2)circulation, movement and connectivity; (3)water management and conservation (4)solid waste and material; (5)community wellbeing strategy; and (6)building and energy, can be applied by combining with various design ideas and responses of site problems. Keywords : Mosque, green architecture, research-based design